Unlocking pre-1850 instrumental meteorological records: A global inventory - BRONNIMANN, Stefan (Institutional Knowledge at Singapore Management University, 2019)
A global inventory of early instrumental meteorological measurements is compiled. It comprises thousands of series, many of which have not been digitized, pointing to the potential of weather data rescue.Instrumental meteorological measurements from periods prior to the start of national weather services are designated “early instrumental data”. They have played an important role in climate research as they allow daily-to-decadal variability and changes of temperature, pressure, and precipitation, including extremes, to be addressed. Early instrumental data can also help place 21st century climatic changes into a historical context such as to define pre-industrial climate and its variability. Until recently, the focus was on long, high-quality series, while the large number of shorter series (which together also cover long periods) received little to no attention. The shift in climate and climate impact research from mean climate characteristics towards weather variability and extremes, as well as the success of historical reanalyses which make use of short series, generates a need for locating and exploring further early instrumental measurements. However, information on early instrumental series has never been electronically compiled on a global scale. Here we attempt a worldwide compilation of metadata on early instrumental meteorological records prior to 1850 (1890 for Africa and the Arctic). Our global inventory comprises information on several thousand records, about half of which have not yet been digitized (not even as monthly means), and only approximately 20% of which have made it to global repositories. The inventory will help to prioritize data rescue efforts and can be used to analyze the potential feasibility of historical weather data products. The inventory will be maintained as a living document and is a first, critical, step towards the systematic rescue and re-evaluation of these highly valuable early records. Additions to the inventory are welcomed.